Formulation of Red Seaweed and Spirulina platensis Based Jelly Drinks - Wini Trilaksani; Iriani Setyaningsih; Dita Masluha (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Generally, jelly drinks in the market contain synthetic sweeteners, coloring and flavoring agents, as well as low in nutrients content, therefore it needs to be developed in order to obtain more healthy product by adding seaweed and Spirulina. The aims of this research were to determine the best formula of jelly drinks with seaweed (Eucheuma cottonii) and Spirulina platensis and to compare the characteristics (nutrients and antioxidant activity) of jelly drinks made from culture-based Spirulina and from commercial Spirulina. Jelly drinks made from commercial Spirulina (0.2%; 0.4%; and 0.6%) had protein content 1.218-2.750% (db) and the IC50 value was 3363.5-6070 ppm. Bayes test showed that jelly drink with commercial Spirulina 0.4% was the selected product and was used as the reference formula on this research. Types of Spirulina (commercial and culture) gave no significant effect (p>0.05) to the hedonic test results and antioxidant activity however affected significantly on protein content (p<0.05). Jelly drink supplemented with 0.4% of culture-based Spirulina produced 92 kcal of energy; meanwhile the jelly drink with 0.4% of commercial Spirulina produced 79 kcal of energy. Keywords: Dietary fiber, jelly drink, protein, seaweed, Spirulina platensis